STUDENT SUPPORT PROGRAM TO REDUCE STRESS, ANXIETY, AND DEPRESSION ON MEDICAL STUDENTS - Nurfitri Bustamam; Ria Maria Theresa; Sri Wahyuningsih (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2020)
Background: Medical education is considered as being stressful which may cause stress, anxiety, and depression. The student support program is designed to help students of the Faculty of Medicine Universitas Pembangunan Nasional Veteran Jakarta (FMUPNVJ) build resilience to the stress through education and coping skills training. This study aimed to evaluate this supportive program on stress, anxiety, and depression levels, as well as academic performance.Methods: This study used a one-group pretest-posttest design. Thirty of third-semester students who were randomly chosen and had psychological problems according to the criteria were offered to join the program. The program used problemfocused coping and emotion-focused coping methods in eight sessions for four weeks. Before and after the program, students were evaluated using the Depression Anxiety Stress Scale-42 questionnaire and their academic performance based on block exam results.Results: Wilcoxon test showed a decrease in levels of anxiety (p = 0.003) and depression (p = 0.004) after the program. There was no difference in stress levels before and after the program (p = 0.073), but there were a tendency stress levels of the subject to be lower after the program. Wilcoxon test showed an increase in the practice exam result (p = 0.000). There was no difference in theory exam results before and after the program (p = 0.358), but there was a tendency that the exam result to be higher after the program.Conclusion: The student support program has an indication for overcoming psychological problems and improving the academic performance of FMUPNVJ students.